2021
DOI: 10.3389/fmed.2021.742713
|View full text |Cite
|
Sign up to set email alerts
|

Update on Cardiovascular Risk and Obesity in Psoriatic Arthritis

Abstract: PsA is characterized by a high prevalence of cardiovascular (CV) comorbidities. Recognizing these comorbidities is critical due to their influence on the quality of life and the choice of therapy. Imaging techniques also play an important role in the evaluation of the CV risk in psoriatic disease, improving the prediction of CV events when combined with clinical scores as a predictive tool. Meta-analyses point to a significant reduction in the incidence of CV events associated with the suppression of inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…This study demonstrated a strong correlation between physiological factors, including increased systolic BP, and anthropometric indices like weight, BMI, WC, weight‐to‐hip ratio, weight‐to‐height ratio, and work capacity as seen in literature 56–58 . This study found that demographic and lifestyle characteristics of age, marital status, BMI, and number of children correlated with job performance as recently submitted by Kaewdok et al 20 that a person's physical attributes like age, weight, and musculoskeletal capabilities and lifestyle variables like leisure‐time physical activity, diet, smoking, and sleep and his job capacity index.…”
Section: Discussionsupporting
confidence: 70%
“…This study demonstrated a strong correlation between physiological factors, including increased systolic BP, and anthropometric indices like weight, BMI, WC, weight‐to‐hip ratio, weight‐to‐height ratio, and work capacity as seen in literature 56–58 . This study found that demographic and lifestyle characteristics of age, marital status, BMI, and number of children correlated with job performance as recently submitted by Kaewdok et al 20 that a person's physical attributes like age, weight, and musculoskeletal capabilities and lifestyle variables like leisure‐time physical activity, diet, smoking, and sleep and his job capacity index.…”
Section: Discussionsupporting
confidence: 70%
“…These data strongly underline the need to carefully screen for and manage the different CV risk factors in PsD. In parallel to CV risk factors, obesity, diabetes and MetS require specific attention in patients with PsD to be adequately managed (7,37,43). Optimal lifestyle modification in PsO including hypocaloric and Mediterranean diet and smoking cessation if required, is a cornerstone of strategies to reduce CV disease (61).…”
Section: Clinical Implications Of Cardiometabolic Conditions In Psd S...mentioning
confidence: 99%
“…Higher cardiovascular (CV) risk is well documented in immune-mediated diseases such as rheumatoid arthritis (RA) or systemic lupus erythematosus ( 6 ). In parallel, there is a growing interest in CV and metabolic diseases in patients with PsD ( 4 , 5 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to classical musculoskeletal and skin manifestations, people with PsA also present with high numbers of CV and metabolic comorbidities (19), a factor that could contribute to the increasing e morbidity and mortality, even if in a recent population-based study the survival rates over 5 years of the PsA patients were comparable with the general population (11) .…”
Section: Discussionmentioning
confidence: 99%